2021
DOI: 10.3390/computers10020021
|View full text |Cite
|
Sign up to set email alerts
|

Deep Feature Fusion of Fingerprint and Online Signature for Multimodal Biometrics

Abstract: The extensive research in the field of multimodal biometrics by the research community and the advent of modern technology has compelled the use of multimodal biometrics in real life applications. Biometric systems that are based on a single modality have many constraints like noise, less universality, intra class variations and spoof attacks. On the other hand, multimodal biometric systems are gaining greater attention because of their high accuracy, increased reliability and enhanced security. This research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Leghari et al [25] compared feature-level fusion strategies on multimodal biometric data and showed that higher accuracy was obtained by performing fusion at the convolutional layer than at the linear layer. Selective fusion networks [26] weight the estimated high-quality information with the original depth information as a whole, but ignore the intra-modal interchannel variability.…”
Section: A Multimodal Biometric Recognitionmentioning
confidence: 99%
“…Leghari et al [25] compared feature-level fusion strategies on multimodal biometric data and showed that higher accuracy was obtained by performing fusion at the convolutional layer than at the linear layer. Selective fusion networks [26] weight the estimated high-quality information with the original depth information as a whole, but ignore the intra-modal interchannel variability.…”
Section: A Multimodal Biometric Recognitionmentioning
confidence: 99%
“…Tiong et al [45] proposed a method of information fusion via extracting features from raw biometric data using a CNN and then combining them with a series of fully connected layers. Other deep learning approaches have been proposed recently [7,53,2,28,44]. Contrasting these methods, we opt for a linear projectionbased approach to limit the multiplicative depth of the circuit and decrease computational complexity, which is important for creating a practical solution in FHE.…”
Section: Related Workmentioning
confidence: 99%
“…Leghari et al [38] discussed the fusion of fingerprint and online signature. The CNN model was developed for early and late feature fusion, and in the early feature fusion obtained an accuracy of 99.1%, and in the late feature fusion obtained an accuracy of 98.35%.…”
Section: Et Al [32] Used Incompletely Closed Nir (Icnir) Finger Capturing Equipment Based On Nir Imaging Technique To Perform Feature-levmentioning
confidence: 99%